Gestational Age at Delivery Is an Independent Predictor of Neonatal Outcome for Maternal HELLP Syndrome - Yan Shi; Xiaoli Yang; Chengqin Wang; Luosong Zhuoga; Dongmei Xu (The Journal of Clinical Hypertension)
Abstract Hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome is a severe complication of preeclampsia (PE), with a higher incidence rate in people living at high altitudes, such as Tibet area. Maternal HELLP syndrome is associated with an elevated neonatal mortality rate. The purpose of this study was to investigate the predicting factors for neonatal outcomes with maternal HELLP syndrome. We collected 49 PE with HELLP cases and stratified them into the Survival Group (n = 28) and Death Group (n = 21) based on the neonatal outcomes. We compared the basic characteristics and laboratory indicators using the Student's t‐test or the Mann–Whitney U test, followed by univariate and multivariate logistic regression analysis to detect the independent predicting factors for neonatal outcomes. Subsequently, we performed the receiver operating characteristics (ROC) analysis to predict the prognostic power of the variables with a cutoff value. The results indicated that levels of neutrophil‐to‐lymphocyte ratio (NLR), serum creatinine (Scr), lactic dehydrogenase (LDH), and brain natriuretic peptide (BNP) were significantly elevated, while gestational age (GA) at delivery and alkaline phosphatase (AP) level was significantly decreased in the Death Group. The multivariate regression analysis indicated that only GA at delivery was able to predict the neonatal outcome. The cutoff value was 32.6 weeks on the ROC curve, with both 85.7% sensitivity and 85.7% specificity (AUC: 0.927, 95% CI: 0.856–0.998, p < 0.001). Thus, it was concluded that GA at delivery less than 32.6 weeks was an independent predictor of neonatal death for maternal HELLP syndrome.